NEW COMING OF THE PUBLIC ADMINISTRATION OF THE SPHERE EXTENDED FAMILY NAMES: REGIONAL ASPECT - Sitnik , S. P (Theory and Practice of Public Administration, 2021)
An analysis of the specifics of the state policy of regional development of the zones of influence of regional systems is collected. The main problems that have arisen in the regions in the field of state family policy are identified. It is revealed that modern global challenges and tendencies together with the indicated problems of regional development of Ukraine predetermine the necessity of elaboration of a new state regional policy, called to overcome the existing threats to existing ones.Modern global challenges and tendencies, together with the identified problems of Ukraine’s regional development, necessitate the development of a new state regional policy aimed at overcoming existing threats, creating and creating new threats to the region. The primary task of scientific research is the analysis of extended family relations, the study of new approaches to public administration in the field of family policy with the establishment of ways to further improve it. Along with the change of approaches to the formation of the state regional policy, it is expedient to update the mechanisms of its implementation. They should be aimed at creating conditions for self-development of regions and clearly meet the set goals. A sufficient variety of mechanisms must also be provided, and more tools, forms and methods of establishing interaction between the subjects of regional policy must appear. To do this, it is necessary to study the experience of other countries, theoretical and practical aspects of the choice and application of mechanisms of the new regional policy, to form databases for their practical use.